IODP Expeditions 304 & 305 Characterize the Lithology, Structure, and Alteration of an Oceanic Core Complex - B. Ildefonse; D. Blackman; B. E. John; Y. Ohara; D. J. Miller; C. J. MacLeod; the IODP Expeditions 304-305 Scientists (Scientific Drilling, 2006)
No abstract available. doi:10.2204/iodp.sd.3.01.2006